DETERMINE THE EFFECT OF PRICE PERCEPTIONS, CONSUMERS, AND BRAND IMAGE ON BRAND BEHAVIOR ON BEAT MOTORCYCLE BRAND USERS IN BIREUEN DISTRICT - Ulia Fitri; Julimursyida; Adnan; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of price perceptions, consumers, and brand image on brand behavior on beat motorcycle brand users in Bireuen district. This study uses primary data obtained by distributing online questionnaires to 100 respondents who were selected using the purposive sampling method. The data analysis method used is multiple linear regression analysis with the help of SPSS version 24. The results partially show that consumer price perceptions and brand image have a significant effect on brand switching behavior from Mio brand motorcycle users to Beat brand motorcycle users in Bireuen district. Simultaneously, the perception of price, consumers and brand image also significantly influence the brand shift of Mio brand motorcycle users to Beat brand motorcycle users in Bireuen district.